ダイ 31 ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1990 - 塚村, 浩二; ツカムラ, コウジ; 岩崎, 明; イワサキ, アキラ; 上林, 正幸; ウエバヤシ, マサユキ; 森本, 正夫; モリモト, マサオ; 柴田, 誠司; シバタ, セイジ; Tsukamura, Kouji; Iwasaki, Akira; et al. (1993)
P(論文) この報告は第31次南極地域観測隊気象部門が, 1990年2月1日から1991年1月31日まで昭和基地において行った地上および高層気象観測と1990年1月1日から12月31日までのあすか観測拠点における地上気象観測の結果並びに1989年11月から12月に行った「しらせ」船上でのオゾン観測結果をまとめたものである。観測方法, 設備, 結果の取り扱い等は, 昭和基地においては第30次観測隊とほぼ同じである。あすか観測拠点においては第31次観測隊から定常観測業務を開始した。観測方法, 設備, 結果の取り扱い等は, 昭和基地と同様にした。あすか観測拠点定常観測開始に伴い日照観測を始めた。また, 南極気候変動研究計画の一環として気水圏研究部門が計画した, オメガゾンデによる高層気象観測を月1回実施した。越冬期間中特記される昭和基地の気象現象としては, 次のものがあげられる。1) 7月はブリザード襲来が9回となり, 気温・風速の各極値を更新した。2) 9月の平均オゾン全量は観測開始以来最低値となった。また, 全般的に冷え込み月平均気温は過去最低値を記録した。3) 1月にはまれなブリザードの襲来により日最大瞬間風速の月の第1位の記録を更新した。 This paper describes the results of surface, upper air and ozone meteorological observations carried out by the Meteorological Observation Team of the 31st Japanese Antarctic Research Expedition (JARE-31) from 1 February 1990 to 31 January 1991 at Syowa Station, surface observations from 1 January to 31 December 1990 at Asuka Station and ozone observations from November to December 1989 on board the icebreaker SHIRASE. The observations, instruments and statistics at Syowa Station were the same as those of the JARE-30 observation team. At Asuka Station, routine surface observations were started with sunshine hour observation from JARE-31,other observations were the same as at Syowa Station. Aerological observations with Omegasonde in the Antarctic Climate Research Program of the Meteorology and Glaciology team were carried out about once a month. The principal characteristics are as follows : 1) In July, blizzards were encountered nine times, and the records of temperature and wind were broken. 2) In September, the monthly mean total ozone amount was the lowest on record. The surface temperatures were always low, and the monthly mean was the lowest on record. 3) In January, an anomalous blizzard in summer was encountered, and the daily maximum wind speed and gust were the strongest on record in January. departmental bulletin paper